FARMERS’ PREFERENCES IN THE RANGE OF ADVISINGIN AGRICULTURAL FARMS IN WĘGRÓW DISTRICT - Marek Niewęgłowski; Tomasz Kacprzak (Annals of the Polish Association of Agricultural and Agribusiness Economists, 2017)
This paper presents preferences whiting the range of thematic area of advising in individual agricultural farmsby agricultural advising centres and private companies. Based on results of questionnaire, carried out in easternMasovian province in Węgrów district, it was stated that majority (75%) of farmers-respondents avail themselvesof state’s advising. Almost 68% of respondents are interested in getting information about helping programmes thataffects positively on farms’ profitableness. Farmers are also concerned about new technologies and farms technicalequipment – 48% of answers. Current situation of polish agriculture constantly requires support from both privateand public advising centres.